2022
DOI: 10.17227/rce.num84-12125
|View full text |Cite
|
Sign up to set email alerts
|

Videojuegos y educación: análisis de tendencias en investigación

Abstract: Mucho se ha escrito en los últimos tiempos acerca de las posibilidades y controversias del uso de los videojuegos en educación. Para conocer las tendencias en investigación, a través de la productividad, impacto, colaboración y difusión, se realizó un análisis bibliométrico sobre 226 documentos disponibles en la base de datos Scopus. Además, se complementó con un análisis de contenido de los 62 artículos disponibles en acceso abierto. Los resultados muestran el interés por el estudio de esta cuestión y el auge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
3
0
0
3
Order By: Relevance
“…With regard to the bibliometric laws, firstly, it is not possible to assess the compliance with Price's law (on the growth of scientific information) with the available data, since the period analysed in this study was limited to three years, because the subject was linked to the COVID-19 pandemic. Secondly, based on Lotka's law, which focuses on the relationship between the number of documents and the of authors writing on a topic, no major producers were identified in this study, as in previous investigations [3]. Thirdly, the distribution of publications in this study is observed in concentric zones of decreasing productivity, following Bradford's law and in line with previous work, such as that of.…”
Section: Discussionsupporting
confidence: 85%
“…With regard to the bibliometric laws, firstly, it is not possible to assess the compliance with Price's law (on the growth of scientific information) with the available data, since the period analysed in this study was limited to three years, because the subject was linked to the COVID-19 pandemic. Secondly, based on Lotka's law, which focuses on the relationship between the number of documents and the of authors writing on a topic, no major producers were identified in this study, as in previous investigations [3]. Thirdly, the distribution of publications in this study is observed in concentric zones of decreasing productivity, following Bradford's law and in line with previous work, such as that of.…”
Section: Discussionsupporting
confidence: 85%
“…With regard to the bibliometric laws, firstly, it is not possible to assess the compliance with Price's law (on the growth of scientific information) with the available data, since the period analysed in this study was limited to three years, because the subject was linked to the COVID-19 pandemic. Secondly, based on Lotka's law, which focuses on the relationship between the number of documents and the number of authors writing on a topic, no major producers were identified in this study, as in previous investigations [59]. Thirdly, the distribution of publications in this study is observed in concentric zones of decreasing productivity, following Bradford's law and in line with previous work, such as that of [27].…”
Section: Discussionsupporting
confidence: 84%
“…We did not identify any major producers, and the distribution of publications in concentric zones of productivity is divided into a well-differentiated core, in line with previous work such as [81]. As in prior studies, we observed a predominance of the fields of social sciences, psychology, and medicine [82], the weight of the USA as a reference country, and English as a vehicular language [83].…”
Section: Discussionsupporting
confidence: 83%